Unusual Case of a Fractured Anconeal Process in a Boxer - Flegel, T.; Kehnscherper, G. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
An acute weight-bearing lameness in the left front limb following a slight trauma happened in a male, one-year-old Boxer. Clinical and radiographic findings suggested a fractured anconeal process.Such a fracture after mild trauma is uncommon and indicates the possibility of a disorder in the area of the growth plate between anconeal process and ulna. Therefore this case could be related to the complex of the ununited anconeal process, too.A one-year-old Boxer sustained a fracture of the anconeal process following a mild trauma. This case might be related to the complex of the ununited anconeal process.
Keywords: Fractured anconeal process; ununited anconeal process; Boxer